ANALISIS PENGARUH LIKUIDITAS, PROFITABILITAS DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP STOCK RETURNS - Gusganda Suria Manda; Anwar Musadad; Meti Nopita (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
This research is a quantitative research. The population in this study is companies owned by state-owned companies listed on the Indonesia Stock Exchange for the period 2013-2018, amounting to 20. Sample selection using purposive sampling techniques and obtained 16 companies as research samples. The type of data used is secondary data. The method of library research or library research and documentation is used as a data collection technique. Data analysis methods used in this research are descriptive statistical analysis, classic assumption test, and hypothesis testing. Data is processed with IBM SPSS Version 22.0 for windows. Based on the results of the study indicate that the variable Net Profit Margin, Return on Equity, and Corporate Social Responsibility have a significant and significant effect on stock returns. Meanwhile, the variable Return on Assets and Price Earning Ratio has no effect on stock returns. The value of the determinant coefficient (R2) produced was 0.444 or 44.4%. This shows that the Net Profit Margin, Return on Equity, and Corporate Social Responsibility variables affect the stock returns of state-owned enterprises listed on the Indonesia stock exchange in the 2013-2018 period that is equal to 44.4%, while the remaining 55.6% is influenced by variables other than research.